2011
DOI: 10.1108/17505931111187785
|View full text |Cite
|
Sign up to set email alerts
|

Managing motives and design to influence web site revisits

Abstract: Purpose -The purpose of this paper is to better understand the relationship between web site design characteristics and revisit intention by examining the roles of satisfaction and consumer motives, thus providing managers with strategies that they can adopt to secure revisiting consumers at their web sites. Design/methodology/approach -This paper uses survey method to collect data from 238 respondents and mediation hypotheses are tested with structural equation modelling using LISREL. Findings -The results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 75 publications
0
17
0
4
Order By: Relevance
“…Recently, researchers (e.g. Beullens & Vandenbosch, 2015;Ha & Janda, 2014;Kabadayi & Gupta, 2011) have adopted the "direct effect model" to understand how online stimuli can influence consumers' responses. They further believe that such investigations may be beneficial in terms of the prediction of online consumer behaviors.…”
Section: Research Modelmentioning
confidence: 99%
“…Recently, researchers (e.g. Beullens & Vandenbosch, 2015;Ha & Janda, 2014;Kabadayi & Gupta, 2011) have adopted the "direct effect model" to understand how online stimuli can influence consumers' responses. They further believe that such investigations may be beneficial in terms of the prediction of online consumer behaviors.…”
Section: Research Modelmentioning
confidence: 99%
“…It has been stated that the success of e-commerce business relies more on users' continued usage intention rather than on their initial adoption (Chou et al 2010;Kabadayi and Gupta 2011). Purchase intention is a dimension of behavioural intentions (Zeithaml et al 1996), and it has been argued that it is the best predictor of action (Dedeke 2016).…”
Section: Relational Variables In Local Food E-commercementioning
confidence: 99%
“…Chung et al (2015) have also confirmed the positive impact of satisfaction on continued usage intentions. As Kabadayi and Gupta (2011) pointed out, a satisfactory perception normally results in a positive attitude toward the website.…”
Section: Relational Variables In Local Food E-commercementioning
confidence: 99%
“…Pengaruh positif web personality terhadap utilitarian web browsing menunjukkan bahwa website personality yang dikembangkan oleh website Lazada sangat menarik perhatian para website visitors yang melakukan kegiatan browsing dengan motivasi utilitarian untuk berkunjung. Website visitors dengan motivasi utilitarian adalah mereka yang cenderung berfokus pada tujuan akhir mereka dalam mengumpulkan informasi (Kabadayi & Gupta, 2011), diantaranya untuk menghilangkan atau mengurangi risiko yang terkait dengan tugas-tugas belanja, penghematan uang dan hasil ini mendukung studi yang dilakukan yang menemukan bahwa system quality, information quality, security dan privacy pada website mempengaruhi perkembangan perceived flow customer, salah satunya web browsing (Ali, 2016).…”
Section: Metode Penelitianunclassified
“…Penggunaan warna, tata letak, animasi, grafis, paparan gambar interaktif dan rangsangan atmosfer lainnya pada website dapat menarik perhatian konsumen untuk mengunjungi website serta mempengaruhi sikap mereka terhadap online store (Manganari, Siomkos, & Vrechopoulos, 2009). Dengan kata lain, pengalaman yang menyenangkan dalam online store akan membuat konsumen menghabiskan lebih banyak waktu, menghabiskan lebih banyak uang untuk melakukan pembelian, dan memiliki keinginan menjalin hubungan baik dengan karyawan online store (Xia, 2010), yang kemudian memicu niat konsumen untuk kembali mengunjungi website (Kabadayi & Gupta, 2011).…”
unclassified